(untitled) (Journal of Student Affairs in Africa, 2024)
Utilizing a social constructivist lens, this study explores how students from rural areas constitute and negotiate their identities within an urban South African University. Much of the research on rurality in South Africa has focused on rural areas as places, and not on the people occupying them. This qualitative study employed a narrative inquiry using the Life Course Theory of Development as its theoretical framework. Data collection comprised a mix of semi-structured questionnaires and focus group interviews. Data was analyzed using content analysis. The findings were threefold: first, in constituting their identities rural students remained grounded in who they were, contrary to literature which found rural students trying to fit into the dominant hegemonic culture of an urban university. The study found that students remain grounded in their rural identities. Second, in negotiating their identities, rural students assumed hyphenated identities-the rural-urban binary-to blend into the urban environment, assuming a ’chameleon identity’ but did not abandon their social-cultural upbringing, philosophy, values, and attributes when they joined an urban institution. They aligned with philosophies that resonated with their upbringing rather than seeking to be assimilated. Third, when they joined an urban university they began to perceive their role as having shifted from being recipients of their background to becoming contributors to its development